Interpretative decisions in the practice of the Constitutional court of Serbia - Rajić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The relationship between the Constitutional court and Parliament is marked by envolving process. The desired balance between these two state bodies was gradually disturbed by the Constitutional court. Consequently, the substrate of the constitutional function originally designed as a function of „negative legislator“ is also changed in that process. Interpretative decision is one of the model of the activity of the Constitutional court which makes questionable the position of the Parliament as a state body which regulates social relations in original form. Interpretative decision is an specific form of rejected decisions that contains binding instruction regading the interpretation of the norm, as a condition. This interpretation is given by Constitutional court in order to make the norm in accordance with the Constitution. By the analysis of the practice of the Constitutional Court of Serbia, the paper has a task to determine wheter, to what extend and in wtah form the interpretative decisions occur in the work of the Court as well as to determine is there a clear constitutional base for establishing the jurisdiction of their adoption in our legal system